Morphological and chemical traits associated with resistance against spotted pod borer, Maruca vitrata in pigeonpea - Jat et al, B L (Indian Journal of Plant Protection, 2018)
Host plant resistance is an important tool for minimizing the losses in pigeonpea due to spotted pod borer, Maruca vitrata, which is the most threatening hidden pest of pigeonpea crop. Experiment was carried out to study the morphological and chemical traits in pigeonpea associated with expression of resistance to M. vitrata and their incidence in different sowing dates. The incidence of M. vitrata varied signifcantly among different sowing dates. Crop sown on D2 (1st week of July) resulted in maximum pod infestation by M. vitrata (13.1%). Minimum pod infestation (2.3%) and (2.9%) was recorded in D4 (3rd week of July) and D1 (3rd week of June) sown crop, respectively. Among different varieties, AL-201 registered lowest pod infestation (4.3%) as compared to Pusa-992 (7.9%). The non-glandular (type A), and glandular (type B) pod trichome density of top, middle and lower canopy of the plant and the pod wall thickness was responsible for the resistance to M. vitrata. Whereas, non-glandular (type C) pod trichomes, pod length, seed width and number of seeds per pod were associated with the susceptibility to spotted pod borer. Expression of resistance to M. vitrata pod infestation was associated with low amounts of crude protein and total soluble sugar and higher amount of fat content, phenol content and tannin content of seed as well as pod wall.